Characterization and biodegradability of extruded foamed polypropylene filled pineapple leaf fiber biocomposites - Rusman, Rafidah (2010)
Polymer foam biocomposites based on Polypropylene (PP)-Pineapple Leaf Fiber (PALF) were successfully produced by an extrusion foaming process. The compounding of PP with PALF was performed in twin-screw extruder which blend the materials with dicumyl peroxide (DCP) and chemical blowing agent (ADC). The DCP (1%) and ADC (1.5%) were kept constant while PALF content were varied from 0% to 30% by weight. After forming the foam, samples was prepared for water absorption test (ASTM D-2842), density determination and biodegradability test (ASTM G21). The PP-PALF biocomposite foam was characterized using Thermogravimetry Analysis (TGA) and Differential Scanning Calorimetry (DSC). It was found that PP-PALF biocomposite foam is open-cell foam and is proved by the water absorption test which increased linearly with increment of PALF loadings. From the DSC result, it was showed that the percent of crystallinity decreases with increased in filler loading and the melting temperature of the PALF-PP biocomposite foam were not much affected by incorporation of PALF. Finally, the additions of pineapple leaf fiber into each formulation have significantly improved the biodegradability of the biocomposites.